Comparing the quality of life and satisfaction with treatment of type 2 diabetes of patients who participated in the Waan Chean Jai which is self-management education and support program of the Saraburi Hospital with type 2 diabetes of patients who did not participate in the project - Pitaksinpanit, Vitchapon (Journal of Medical and Public Health Region 4, 2020)
The objective of this research was to study the quality of life and satisfaction with treatment of type 2 diabetes of patients who participated in the Waan Chean Jai which is self-management education and support project of the Saraburi Hospital comparing with type 2 diabetes of patients who did not participate in the project. The research model was a cross-sectional analytical study by using the sample groups 206 persons which can be divided into 2 groups as follows: 1.Participated program at least 3 months 2.Not participated pagram. The used instruments were Audit of Diabetes Dependent Quality of Life 19 (ADDQoL19) and Diabetes Treatment Satisfaction Questionnaire (DTSQ). The finding revealed that type 2 diabetes of patients who participated in the Waan Chean Jai which is self-management education and support project of the Saraburi Hospital had the average blood sugar level after fasting for 8 hours (FBS), the cumulative average of the sugar backward (HbA1C) accumulated were at a higher level more than patients who did not participate in the project at a statistically significant with a P-Value <0.001 and <0.001 respectively. In addition, patients who participated in the project had a higher level of the mean and average quality of life than patients who did not participated in the program(p<0.001) and found that the overall satisfaction from treatment was higher than patients who did not participate in the activity at a statistically significant with a P-Value of less 0.001 Therefore, doctors and the related personnel should educate people with diabetes and strengthen their diabetes care skills in combination with general diabetes treatment so that patients can control their blood sugar levels according to their goals and enhance the quality of life, including satisfaction with existing diabetes treatment and reducing future in current disease of patients.